Assessment of a residential building in terms of carbon footprint and circular economy - Budajova Jana; Vilcekova Silvia; Burdova Eva Kridlova; Mesaros Peter (Selected Scientific Papers: Journal of Civil Engineering)
Built environment contributes significantly to social and economic development, but it is also resource intensive. It is therefore one of the main producers of emissions and carbon footprint. Choosing building designs with a long service life is the key to resolving environmental problems. In this paper, the life cycle of a residential building is evaluated to reduce the greenhouse gas emissions and costs associated with the construction, use and disposal of the building. Life Cycle Assessment and Life Cycle Costing methods were used to evaluate the environmental and financial impact of the residential building. The system boundaries were defined as “Cradle to Grave” and a lifetime of 60 years. The calculation showed that the building emitted 843 tons of CO2e, or 19.8 kg CO2e/m2/year, and the life cycle costs were 2 026 €/m2. Considering the phases considered, the energy consumption phase (B6) caused the highest CO2e emissions, up to 50.1%.